Privacy concerns and consumers’ trust in m-commerce Apps in Malaysia - Nur Hikmah Masrana; Azaze Azizi Abdul Adis (Penerbit UMS, 2024)
Apps for mobile devices have become crucial in daily life. Every day, millions of people rely on smartphone apps to perform a variety of crucial tasks. Mobile app shops have seen an expansion in the number of apps due to rising consumer demand. On the other hand, as people's concerns about online privacy have grown, privacy issues pertaining to internet use have become more important in recent years. However, this study found that building trust might help allay consumers' worries about privacy when it comes to using m-commerce apps in Malaysia. Consequently, the purpose of this study is to empirically investigate customers' trust by comprehending privacy concerns related to their use of mcommerce apps in Malaysia. The APCO model and Social Cognitive Theory (SCT) are further explored in this study. Data were gathered through an online survey conducted on Malaysian users of mobile applications. Only 292 of the 350 respondents' useful responses were examined using SPSS and SmartPLS statistical tools. The results demonstrated and validated (APCO) and (SCT) emphasis on people examining the risks and benefit when deciding whether to disclose personal information. Practitioners would apply the empirical findings to study and comprehend consumer preferences in light of these results.